Agricultural Water Conservation: Tools, Strategies, and Practices - Montazar, Aliasghar (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Water scarcity is a critical issue for agriculture, and, hence, efficient management and conservation practices for agricultural water use are essential for adapting to and mitigating the impacts of current and future discrepancy between water supplies and water demands. This Special Issue focuses on "Agricultural Water Conservation: Tools, Strategies, and Practices", which aims to bring together a collection of recent cutting-edge research and advancements in agricultural water conservation. The Special Issue intends to give a broad overview focusing on on-farm water conservation practices, advanced irrigation tools and water technologies, and the best management practices and strategies for efficient water use in agriculture.